2008
DOI: 10.1534/genetics.107.080903
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Functional Divergence Among Triplicated α-Globin Genes in Rodents

Abstract: The functional divergence of duplicated genes is thought to play an important role in the evolution of new developmental and physiological pathways, but the role of positive selection in driving this process remains controversial. The objective of this study was to test whether amino acid differences among triplicated a-globin paralogs of the Norway rat (Rattus norvegicus) and the deer mouse (Peromyscus maniculatus) are attributable to a relaxation of purifying selection or to a history of positive selection t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 107 publications
2
26
0
1
Order By: Relevance
“…The pattern of gene turnover has been especially well characterized in the a-globin gene cluster of mammals (Zimmer et al, 1980;Hoffmann et al, 2008a;Storz et al, 2008). Electrophoretic surveys of genetic variation at the HBA locus in natural and domestic populations of the European rabbit had previously revealed a pattern that was consistent with the existence of a single HBA gene, as reported by Cheng et al (1986).…”
Section: Copy Number Polymorphism and Hybridization R Campos Et Almentioning
confidence: 74%
See 1 more Smart Citation
“…The pattern of gene turnover has been especially well characterized in the a-globin gene cluster of mammals (Zimmer et al, 1980;Hoffmann et al, 2008a;Storz et al, 2008). Electrophoretic surveys of genetic variation at the HBA locus in natural and domestic populations of the European rabbit had previously revealed a pattern that was consistent with the existence of a single HBA gene, as reported by Cheng et al (1986).…”
Section: Copy Number Polymorphism and Hybridization R Campos Et Almentioning
confidence: 74%
“…Comparative genomic studies have revealed extensive variation in the size and membership composition of the a-and b-globin gene families in mammals (Hoffmann et al, 2008a, b;Storz et al, 2008;Opazo et al, , b, 2009. In principle, studies of gene copy number variation within species could provide insights into the evolutionary forces that have shaped the observed copy number variation among species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the bank vole sequences, we also included published sequences of a-globin genes from the species analysed by Storz et al (2008), that is, P. maniculatus, R. norvegicus and M. musculus. As in the study of Storz et al (2008), a sequence of the single HBA gene of the guinea pig (Cavia porcellus) was used as outgroup (Fabre et al, 2012).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…As in the study of Storz et al (2008), a sequence of the single HBA gene of the guinea pig (Cavia porcellus) was used as outgroup (Fabre et al, 2012).…”
Section: Phylogenetic Analysismentioning
confidence: 99%
See 1 more Smart Citation